Peran Majelis Taklim dalam Meningkatkan Religiusitas Masyarakat Melalui Kajian Kitab Rutinan di Desa Suci Kecamatan Panti Kabupaten Jember - Siti Humairoh (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2021)
The Taklim assembly is a forum for the community in order to gain knowledge about Islam, which is more open and usually carried out routinely. Therefore, the delivery of da'wah must also be adjusted to the local conditions of the community, the aim of which is to be easily understood and accepted by the community itself. This research will describe the role of the taklim assembly in increasing the religiosity of the community, how enthusiastic the community is in the taklim assembly, and what books are used as references in delivering their da'wah. This research is categorized in the type of qualitative-descriptive research with the methods of observation, interviews, and documentation, which in the future is expected to obtain more comprehensive data. The results of this study indicate that: 1) the taklim assembly, especially in the Suci-Panti Village, plays an important role for the community itself as in terms of religiosity which is basically reflected in the practice of aqidah, sharia, and morals (faith, Islam, and ihsan). In the taklim assembly which is held every Monday night Tuesday, it gets a very good response from the community, even the community is very enthusiastic when the study takes place, besides that in the assembly a discussion session is held. 2). The books that are used as references in the assembly consist of; aqidatul awam, mabadi'ul fiqhiyah, and lubabul hadith, which are discussed in depth.